Fiscal and Monetary Policy of Economic Development - Chugunov, Igor; Pasichnyi, Mykola; Koroviy, Valeriy; Kaneva, Tetiana; Nikitishin, Andriy (European Journal of Sustainable Development, 2021)
Fiscal and monetary policy coordination should focus on increasing public welfare and maintaining long-term macroeconomic stability. This article aims to enhance the theoretical and methodological basis of fiscal and monetary policy formation and determine the priority areas for improving their coordination to ensure sustainable economic development. We developed an institutional approach to study the fiscal-monetary mix. It is advisable to create favorable monetary conditions for fiscal measures and form a balanced budget for monetary regulation. The authors proposed the structural-functional model that highlights both fiscal and monetary policies’ impact on aggregate demand. The results showed no positive effects of general government expenditures on the GDP per capita growth in 19 emerging economies from 1995 to 2018. The influence of public spending on economic growth depends on institutions’ quality, the composition of expenditures, and fiscal architecture. The expediency of increasing the share of productive expenditures that positively affect stimulating the economy is substantiated. In the long-run, monetary policy should ensure a comprehensive combination of inflation targeting conditions, the adaptive use of tools to achieve intermediate and final targets.